Tecnología de secado aplicado a alimentos y nutrientes - Saavedra Amasifuén, Llily Estefany (2022)
Drying is a method to preserve fruits, vegetables and fish by reducing their volume, their weight. Drying involves the application of energy to vaporize and mobilize the moisture content within porous products. During this process, heat and mass transfer occur simultaneously. The quality of dehydrated fruits, vegetables, and aromatic herbs is a problem closely related to the development and optimization of new drying techniques. This research work addresses the common drying methods applied to fruits, grains, fish and nutrients in relation to possible options to improve the quality of dried products using different drying techniques or their combination. In general, the drying technique is different for each of the materials studied and specific conditions should be recommended after a proper evaluation of the drying protocols. However, a novel or combined technique must ensure a high quality of the dried products. In addition, the term quality must encompass energy efficiency and environmental impact that leads to the production of sustainable dehydrated products. Drying is the process of removing water, usually driven by heat, from solid and liquid products. Resulting in dry solid products. Within a fresh food there are two types of humidity, firstly, the limit humidity characterized by the liquid retained in the microstructure of the solid part and secondly, the unlimited humidity represented by the excess of limited water. Bound moisture is represented by a liquid solution held in a solid matrix. This leads to the coexistence of complex processes during the thermal drying of fresh food products.